The Role of Social Relational Emotions for Human-Nature Connectedness - Petersen, Evi; Fiske, Alan Page; Schubert, Thomas W. (Frontiers in Psychology, 2019)
Little is known about the psychological processes that can explain how connectedness to nature evolves. From social psychology, we know that emotions play an essential role when connecting to others. In this article, we argue that social connectedness and connectedness to nature are underpinned by the same emotions. More specifically, we propose that social relational emotions are crucial to understanding the process, how humans connect to nature. Beside other emotions, kama muta (Sanskrit: being moved by love) might play a particular crucial role when connecting to nature. Future research should address the consideration of social relational emotions in a range of areas when investigating the human-nature relationship.